"When they came to take my father" voices of the Holocaust (Arcade Publ., 1996)
Captured here with clarity and truth are fifty images of survival, portraits of the men and women who lives through the brutality to triumph over oppression: survivors truly. Their wrenching first-person accounts accompany intimate photographs and tell of experiences with an immediacy that is both mesmerising and appalling.